2014
DOI: 10.1038/ncomms4677
|View full text |Cite
|
Sign up to set email alerts
|

Social heuristics shape intuitive cooperation

Abstract: Cooperation is central to human societies. Yet relatively little is known about the cognitive underpinnings of cooperative decision making. Does cooperation require deliberate self-restraint? Or is spontaneous prosociality reined in by calculating self-interest? Here we present a theory of why (and for whom) intuition favors cooperation: cooperation is typically advantageous in everyday life, leading to the formation of generalized cooperative intuitions. Deliberation, by contrast, adjusts behaviour towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

56
631
7
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 627 publications
(711 citation statements)
references
References 74 publications
56
631
7
4
Order By: Relevance
“…We further note that, in contrast with some previous studies (4), our experimental design does not distinguish between the time required to evaluate the choice options and that required to register the decision. Stronger evidence comes from a recent study showing that that time pressure increased prosocial behavior in an extraction game where actions were harmful but outcomes were rewarding (34). Disentangling how the valence of actions vs. outcomes shapes the relationship between deliberation and prosocial preferences is an important direction for future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further note that, in contrast with some previous studies (4), our experimental design does not distinguish between the time required to evaluate the choice options and that required to register the decision. Stronger evidence comes from a recent study showing that that time pressure increased prosocial behavior in an extraction game where actions were harmful but outcomes were rewarding (34). Disentangling how the valence of actions vs. outcomes shapes the relationship between deliberation and prosocial preferences is an important direction for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deciders knew that the roles were fixed, and that the receiver would not have any opportunity to retaliate against the decider's choices. These steps were taken to minimize any potential influence of conscious motivations for reciprocity and avoiding punishment, although we acknowledge that unconscious or habitual motivations for reputation or reciprocity could potentially spill over into putatively anonymous decisions (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this evolved psychology may invoke responses that are attuned to these conditions even in that are not adaptive in truly anonymous, caused by the mis-firing of psychological mechanisms adapted to deter defecting partners from future defection, even when this function is (due to the nature of the game) impossible to achieve. Previous work has shown that when players are put under time pressure to make decisions in one-shot games, they are more likely behave cooperatively (Rand et al, 2014;Rand, Greene, & Nowak, 2012). Similarly, other studies also using one-shot games have shown that when players are given a cooling off period they are less likely to punish cheating partners (Grimm & Mengel, 2011;Smith & Silberberg, 2010;Sutter, Kocher, & Strauß, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…This is even more interesting in the light of emergence of complexity as individuals interact. The studied logit rule model is essential to the emergence of the patterns shown here, and recent research shows the importance of integrating innovative dynamics in game theoretical models, especially since humans seem to use different rules than simply imitating the best when playing evolutionary games [67][68][69]79,[108][109][110][111]. We hope that this paper will motivate further research along this area in the future.…”
Section: Discussionmentioning
confidence: 99%